A counter-narrative analysis of psychological riot in contemporary painting - Ng'ok, Ivy Chemutai (Rhodes University, Faculty of Humanities, Department of Fine Art, 2018)
I am rioting against a system of my own beliefs about the world. In my mind, I struggle to overcome these beliefs, hence, I construct the psychological riot as 'the disturbance of the mind'. In this mini-thesis, I argue that it exists in the psyche too. This definition of psyche becomes painterly. My psychological riot is difficult to trace, let alone paint. The beliefs that I target are patriarchy within a post-colonial context. I use theories that are simultaneously psychological and corporeal. They address violence colonialist system. The psychological riot is an practical submission.
Keywords: Painting -- South Africa; Painting -- Psychological aspects; Distress (Psychology) in art; Imperialism in art; Violence in art; Patriarchy in art Political art